CFTR Deficiency Affects Glucose Homeostasis via Regulating GLUT4 Plasma Membrane Transportation - Gu, Junzhong; Zhang, Weiwei; Wu, Lida; Gu, Yuchun (Frontiers in Cell and Developmental Biology, 2021)
Cystic Fibrosis (CF) is an autosomal recessive disorder caused by mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene. CF-related diabetes (CFRD) is one of the most prevalent comorbidities of CF. Altered glucose homeostasis has been reported in CF patients. The mechanism has not been fully elucidated. Besides the consequence of pancreatic endocrine dysfunction, we focus on insulin-responsive tissues and glucose transportation to explain glucose homeostasis alteration in CFRD. Herein, we found that CFTR knockout mice exhibited insulin resistance and glucose tolerance. Furthermore, we demonstrated insulin-induced glucose transporter 4 (GLUT4) translocation to the cell membrane was abnormal in the CFTR knockout mice muscle fibers, suggesting that defective intracellular GLUT4 transportation may be the cause of impaired insulin responses and glucose homeostasis. We further demonstrated that PI(4,5)P2 could rescue CFTR related defective intracellular GLUT4 transportation, and CFTR could regulate PI(4,5)P2 cellular level through PIP5KA, suggesting PI(4,5)P2 is a down-stream signal of CFTR. Our results revealed a new signal mechanism of CFTR in GLUT4 translocation regulation, which helps explain glucose homeostasis alteration in CF patients.